Process optimization for phosphorus removal with ferric salt by response surface methodology - ZHANG Meng; YU Xiao-qing; QIU Lin; LU Hui-feng; ZHENG Ping (浙江大学学报. 农业与生命科学版, 2012)
Currently eutrophication has become a hot issue all over the world. The removal of phosphorus from wastewaters is regarded as an important approach to fight eutrophication since phosphorus is one of the main factors causing eutrophication. The chemical phosphorus removal technology with ferric salt as a precipitant is in widespread use to meet the wastewater discharge standard. The optimization of phosphorus removal technology helps to cut down the cost of wastewater treatment. Herein the response surface methodology (RSM) is introduced to investigate the individual and combined effects of operation parameters.The performance of chemical phosphorus removal technology with ferric salt as a precipitant is dependant on a series of factors. Fe/P ratio, pH and flash mixing speed (FMS) were chosen as objects of study, and single-factor experiment and multiple-factor experiment were carried out to optimize the phosphorus removal efficiency.The results of single-factor experiment showed that both Fe/P ratio and pH had significant effects on phosphorus removal, but FMS did not. When the phosphorus concentration was 100 mg/L, the optimal operation parameters were Fe/P ratio 3.0, pH 8.0, FMS 175-225 r/min. The results of multiple-factor experiment showed that the individual effects of operation parameters on phosphorus removal were in order as Fe/P > pH > FMS. The combined effects of operation parameters were in order as Fe/P-FMS > pH-FMS > Fe/P-pH, among which the effects of Fe/P-FMS and Fe/P-pH were positive and the effect of pH-FMS was negative. Based on the experiment, “priority/combination” model was proposed to enhance the phosphorus removal with ferric salt as a precipitant. The optimal operation parameters were as follows: Fe/P=2.57, pH=6.31 and FMS=136 r/min, when the phosphorus concentration was 100 mg/L. Both synthetic and real wastewaters were used to verify the feasibility of priority/combination" model. Operated according to the model, the phosphorus removal was larger than 97% and the fractional error was less than 3%.It can be concluded that the response surface methodology is feasible for the optimization of operation parameters in wastewater treatment processes. The priority/combination" model is effective for the improvement of phosphorus removal from wastewaters with ferric salt as a precipitant. During the wastewater treatment, the synergic action of operation parameters should be fully used, while the antagonistic action of operation parameters should be carefully avoided.